Implementasi Nilai Tri Hita Karana dalam Kebijakan Penanganan Pandemi Covid-19 di Provinsi Bali - Kusuma Putri; I Putu Adi Permana Putra (Journal of Contemporary Public Administration, 2022)
The global health crisis due to the Covid-19 pandemic has an impact on various lines of life. This problem requires a solution in acting and responding to the challenges faced, one of them is through policy. Various government products in the form of public policy have been presented to respond to the rapidly growing pandemic. To maximize the policy performance, it is necessary to actualize the values of local wisdom to participate in the form of synergies to overcome the problems of society. Cultivating value that flourish in the community is prominent to be applied for policies to strengthen community resilience and optimize policy implementation. The value of life that arises in the community is an effort to attain policy effectiveness in dealing with challenges and obstacles due to the Covid-19 pandemic. The method used in this study uses a qualitative descriptive approach. The data collection technique used by a literature study with a research focus to describe and analyze the philosophical values of Tri Hita Karana in regional policies as a form of civilizing local wisdom. The results of this study indicate that policy instruments in answering problems must be able to revive the values ​​that exist in the society. The form of dissemination between policies and local wisdom values becomes a symbiosis that supports each other and can establish a more adaptive ecosystem and answer the challenges faced by local communities. The implementation of the Gotong Royong Task Force (Satgas) policy based on Traditional Villages in Bali by integrating the philosophical values of Tri Hita Karana has been able to respond the neccesities of the local community in dealing with the COVID-19 pandemic and is a form of cultivating the Tri Hita Karana values that are implementable and inherit the values of the Tri Hita Karana local wisdom for future generations.